1989
DOI: 10.7326/0003-4819-110-3-208
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein e (LDL) Distribution Shown by ^99mTechnetium-LDL Imaging in Patients with Myeloproliferative Diseases

Abstract: These results indicate that spleen and bone marrow are sites of LDL catabolism in patients with myeloproliferative disease and suggest the role of macrophages in the hypocholesterolemia and accelerated LDL catabolism of myeloproliferative disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In myeloproliferative diseases, on the other hand, decreased LDL is associated with increased clearance of LDL (Ginsberg, Le, Gilbert, Le, & Brown, 1986;Vallabhajosula et al, 1989). Lymphomas, leukemia, and other malignancies have increased levels and increased activity of LDL receptors, which avidly bind and take up LDL, thus reducing their concentra tion.…”
Section: Mechanisms Underlying Hypocholesterolemiamentioning
confidence: 99%
“…In myeloproliferative diseases, on the other hand, decreased LDL is associated with increased clearance of LDL (Ginsberg, Le, Gilbert, Le, & Brown, 1986;Vallabhajosula et al, 1989). Lymphomas, leukemia, and other malignancies have increased levels and increased activity of LDL receptors, which avidly bind and take up LDL, thus reducing their concentra tion.…”
Section: Mechanisms Underlying Hypocholesterolemiamentioning
confidence: 99%
“…6,7 Accordingly, we focused on serum albumin and cholesterol levels because of their known susceptibility to the effects of myelofibrosis-associated inflammatory cytokines and their global applicability. [8][9][10][11] The phenomenon of markedly decreased cholesterol levels in myelofibrosis has long been recognized, 12 and its prognostic relevance has been highlighted in multiple abstracts. [13][14][15][16] More recent reports have suggested a similar scenario with serum albumin.…”
Section: Introductionmentioning
confidence: 99%
“…In PV several studies have demonstrated reduced serum levels of total-, HDL-and LDLcholesterol, and LDL degradation is increased via both LDL-receptor and non-receptor pathways (13)(14)(15). The spleen and bone marrow have been shown to be the major sites of LDL catabolism in PV in contrast to healthy controls in which LDL is primarily degraded in the liver (16). Nevertheless, it has recently been shown in patients with familial hypercholesterolaemia that LDL receptor activity is not a major determinant of Lp(a) plasma levels (17).…”
mentioning
confidence: 99%